An Analysis of Language Styles used by The Main Character in “The Great Debaters” Movie - Indahsari, Fernanda Ega; Rezeki, Yanti Sri; Rahmani, Eka Fajar (Kirana Publisher (KNPub), 2023)
This research was conducted in order to know the types of language styles and the dominant type of language styles used by the main character in The Great Debaters movie. This research used descriptive research approach to analyze the subject. This research used theory by Martin Joos (1976) to find the language styles in the main character’s utterances in the movie. The result showed that there are 48 data found from the main character’s utterances. The details of language styles found in the main character’s utterances in the movie were 0 data for Frozen Style, 7 data for Formal Style, 30 data for Consultative Style, 8 data for Casual Style, and 3 data for Intimate Style. The dominant type of language style used by the main character in The Great Debaters movie is Consultative Style with 30 data found. Also, there were 3 factors that influenced the language styles in the main character’s utterances in the movie, they were the Participants, the Setting, and the Topic.